Split Iterative and Sequential Multicast Scheduling for IQ Switches - Zarar, Shuayb (IEEE Int. Conf. Information, Communications & Signal Processing (ICICS), 2007)
The objective of this work is to design and implement controlled (weighted round robin matching, WRRM) and sequential iterative schemes for weight based multicast traffic scheduling in input-queued (IQ) switches. Motivated by the practical synthesis of a scheduler for a 64-port optical crossbar switch, we demonstrate that limited and sequential iterations in the weight based arbiter (WBA) lead to adjustable clock speeds and configurable designs with flexible control in the performance characteristics close to the conventional WBA. Our FPGA sizing experiments and clock speed evaluations show improvements of upto 46.48% and 19.12%, respectively, over the WBA. In addition, latency-throughput results for the proposed variations, highlight the trade-offs between fairness, throughput, hardware complexity and speed.